Mechanical response of externally bonded CFRP on repair of PCCPs with broken wires under internal water pressure. (10th April 2020) - Zhai, Kejie; Fang, Hongyuan; Fu, Bing; Wang, Fuming; Hu, Benyue
Highlights: Externally bonded CFRP on repair of PCCPs with broken wires were investigated. Effects of wire breakage rates and CFRP layers were considered. A full-scale model test was conducted. Reasonable accuracy of experimental results compared to the simulation results. Abstract: Prestressed concrete cylinder pipe (PCCP) is one of the most widely used long-distance water pipeline forms, and wire breakage is the most common form of PCCP damage. If left unreinforced, the PCCP with broken wires are highly vulnerable to accidents, such as pipe cracking. However, it is difficult to repair broken PCCPs serving as water mains by shutting down the pipe service. Thus, a new method for PCCP in-service repair by external bonding with carbon fiber reinforced polymer (CFRP) layers was proposed in this study. A three-dimensional numerical model of the repair of PCCPs with broken wires using externally bonded CFRP layers was built using the finite element software package ABAQUS. With this model, the case when the total wire breakage rate is 10% but the breakage locations are varied and distributed was studied. Then, the stress–strain features of various structural layers of the PCCPs with broken wires before and after repair with different wire breakage rates (5%, 10%, 15%, and 20%) and different CFRP layers (two, four, six, and eight) were analyzed. The results indicated that CFRP contributed more with higher wire breakage rates. The repair effect was enhanced as the number of repair layers increased. Lastly, a PCCP with an inner diameter of 2.8 m was used as a full-scale internal water pressure model test to investigate the strain responses of various PCCP materials and CFRPs. The experimental results agreed well with the simulated results.